2015
DOI: 10.3389/fmicb.2015.00388
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects on dendritic cells by human herpesvirus 6

Abstract: Human herpesvirus 6A and 6B are β-herpesviruses approaching 100% seroprevalance worldwide. These viruses are involved in several clinical syndromes and have important immunomodulatory effects. Dendritic cells (DC) are key players in innate and adaptive immunity. Accordingly, DC are implicated in the pathogenesis of many human diseases, including infections. In this review the effects of HHV-6 infection on DC will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Given that HHV‐6A can infect oligodendrocytes, it is possible that it directs the immune system against this host cell by incorporation of host cell proteins and lipids in its membrane [32] and thus specifically directs the immune system against the oligodendrocytes. However, upon inoculation with HHV‐6A the most potent activator of T‐cells (i.e., dendritic cells) lose their capacity to activate T‐cell proliferation [33,34] suggesting that the hypothesis of host cell protein incorporation and molecular mimicry, which requires that the virus constitutes an adjuvant effect, is somewhat problematic. Fortunately, the virus is not able to completely avoid immune detection and serological responses are indeed mounted against HHV‐6A, as seen in the present study as well as previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given that HHV‐6A can infect oligodendrocytes, it is possible that it directs the immune system against this host cell by incorporation of host cell proteins and lipids in its membrane [32] and thus specifically directs the immune system against the oligodendrocytes. However, upon inoculation with HHV‐6A the most potent activator of T‐cells (i.e., dendritic cells) lose their capacity to activate T‐cell proliferation [33,34] suggesting that the hypothesis of host cell protein incorporation and molecular mimicry, which requires that the virus constitutes an adjuvant effect, is somewhat problematic. Fortunately, the virus is not able to completely avoid immune detection and serological responses are indeed mounted against HHV‐6A, as seen in the present study as well as previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Both the molecular mimicry and the host cell incorporation model relies on the idea that HHV-6 virion can trigger the T cell stimulatory capacity of APC. However, we and others have shown that inoculation of DC with both HHV-6A and HHV-6B instead hamper the capacity of DC to activate T cells, both in absence and presence of viral replication, and for both allogenic and autologous T cells ( 74 79 ). Hence, HHV-6 induced pathogenesis in MS does not seem to occur through neither of these models.…”
Section: Hhv-6 In Msmentioning
confidence: 72%
“…However, DC can also be targets for viral infections, and with their antigen capturing capacity may be exposed to large amounts of virions. HHV-6A and 6B are very successful viruses that most people have been exposed to, as seen with a high seroprevalence in the human population [ 9 ] and have developed various specific viral immune-escape mechanisms that can hamper the ability of DC to activate T cells [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%